AMACR is a highly sensitive and specific immunohistochemical marker for diagnosing prostate cancer on biopsy: a systematic review and meta-analysis - Johannes Cansius Prihadi; Stevan Kristian Lionardi; Nicolas Daniel Widjanarko; Steven Alvianto; Fransiskus Xaverius Rinaldi; Archie Fontana Iskandar (Journal of Pathology and Translational Medicine, 2025)
Background Alpha-methylacyl-CoA racemase (AMACR) is the preferred biomarker for distinguishing malignant from benign glands in prostate biopsies, showing high sensitivity and specificity for prostate cancer. A meta-analysis of immunohistochemistry (IHC) for AMACR is essential to further assess its diagnostic accuracy across diverse sample sources. Methods A systematic search of databases including MEDLINE, ScienceDirect, ProQuest, Google Scholar, and the Cochrane Library was performed, focusing on studies of AMACR to diagnose prostate cancer, particularly in biopsy samples analyzed through IHC over the last 20 years. Quality of studies was assessed using the Quality Assessment of Diagnostic Accuracy Studies 2 tool, followed by a meta-analysis of regions and subgroups to calculate summary estimates of diagnostic test accuracy. Results In the final analysis, 37 studies, with a pooled size of 5,898 samples, were included from the examination of 94 full-text papers. Among them, 27 studies with similar sample sources and testing methodologies underwent meta-analysis, yielding a combined sensitivity estimate of 0.90 (95% confidence interval [CI], 0.86 to 0.93) and specificity of 0.91 (95% CI, 0.83 to 0.95), both with significant heterogeneity (p < .01). The region beneath the hierarchical summary receiver operating characteristic curve was 0.95 (95% CI, 0.93 to 0.97), positive likelihood ratio was 9.6 (95% CI, 5.3 to 17.4), negative likelihood ratio was 0.11 (95% CI, 0.08 to 0.15), and diagnostic odds ratio was 88 (95% CI, 42 to 181). Conclusions Our meta-analysis findings substantiate AMACR as a highly accurate tool for diagnosing prostate cancer, specifically in biopsy samples, via immunohistochemical staining. Further studies involving diverse samples are needed to enhance our understanding of the AMACR diagnostic accuracy in a range of clinical settings.